Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

If x does not equal -y is (x-y)/(x+y)>1? [#permalink]

Show Tags

07 Jul 2013, 16:47

Hey Guys,

I really need help on the thought process with DS not necessary how to solve the problem. I have a hypothetical DS below. The goal of my question isn't to solve the problem but to find what necessary information is need to begin with to solve the problem.

===============================Question 1================================ If x does not equal -y is (x-y)/(x+y)>1?

(1) y<0 (2) x+y>0

Lets take the two scenarios:

a) If x+y>0 which implies (x-y)>(x+y) ---> y>0 b) If x+y<0 which implies (x-y)<(x+y) ----> y<0

Now Statement (1) in the DS meets scenario (b)'s criteria. So does it make it sufficient? If we know y<0 does this imply x+y<0 and therefore (x-y)/(x+y)>1?

When we use multiple "if-then" scenarios does the questionmark on the statement still extend? In other words should statements (a) & (b) correctly be

(x-y)/(x+y)>1 ?? a) If x+y>0 which implies (x-y)>(x+y) ?? ---> y>0 ?? b) If x+y<0 which implies (x-y)<(x+y) ?? ----> y<0 ??

========================================Question 2========================= To illustrate the point further he is another example: Is x^2-y^2<0?

(1) |x|<|y| (2) x+y>0

Is x^2-y^2<0? can be reworded as x^2<y^2 ?? sqrt(x^2)<sqrt(y^2) ?? |x|<|y| ??

Notice how the question mark extended all the way down as we manipulated the question to get the new question is |x|<|y| ??

In our first statement (1) |x|<|y| matches our question. Hence sufficient.

Is this logic of extending the question mark the same for "if-then" scenarios?

Re: If x does not equal -y is (x-y)/(x+y)>1? [#permalink]

Show Tags

08 Jul 2013, 01:37

Lets just consider the left hand side of the inequality:

(x-y)/(x+y),

1) y < 0 , the left hand side of the numerator can now be rewritten as : (x+ |y|) / (x-|y|). We can still not say that the numerator is larger than the denominator as we still do not know the value of x e.g. , if x=-4 , y = -1

then , (x-y)/(x+y) = -3/-4 = 3/4 (<1)

if x =4 , y = -1

then , (x-y)/(x+y) = 5/3 (>1)

So this is insufficient

2) x+y > 0

=> x > -y this is insufficient too

but if consider 1 and 2 together

from the second statement we have , x > -y ans since y < 0

x > |y|

So both statements are needed to prove the inequality

Re: If x does not equal -y is (x-y)/(x+y)>1? [#permalink]

Show Tags

09 Jul 2013, 00:43

alphabeta,

Let me first present how this problem is intended to be solved by the test writers and then I will examine your approach.

When you see a question like Is (x-y)/(x+y)>1?, then one should always try to simplify or rewrite this by bringing all the terms to one side to make > 0 or < 0. It is always easier to examine if an expression is positive or negative as opposed to comparing two quantities, as is the case in the original question. This is a standard set up on the GMAT.

If we rewrite the above expression as: (x-y)/(x+y) - 1 >0 and clean it up, we end up with Is 2y/(x+y) < 0 ? This is a lot easier to deal with.

Statement 1: (1) y<0 Just use simple examples: x = -2 and y = -3, Answer is No, x = 3 and y = -2, Answer is Yes. Insufficient.

Statement 2: (2) x+y>0 Again use examples: x = 2 and y = 3, Answer is No, x = 4 and y = -2, Answer is Yes. Insufficient.

Statement 1 and 2: This is easy because now we know that the numerator is negative and denominator is positive. Answer is a definite Yes. Sufficient.

One could do this problem in the original form using examples, but that is typically harder. The GMAT is testing your ability to rephrase the question and simplify everything before using examples. This is a classic GMAT set up.

===============================Question 1================================ If x does not equal -y is (x-y)/(x+y)>1?

(1) y<0 (2) x+y>0

Here you are rephrasing the original question under two cases, the first where x+y is positive and the second when x+y is negative. In both cases the resulting simplification is still a question. I have modified it below.

a) If x+y>0 then Is y>0? (this is the new question) or b) If x+y<0 then Is y<0? (this is the new question)

Statement 1 tells us that y<0, the original question is still Is y>0 if x+y>0 and Is y<0 if x+y<0? This is of course getting convoluted but we will pursue this further.

Based on your approach the fact given in statement 1 does not make it sufficient, because if y<0, then I can choose x to be sufficiently positive such that x+y>0 and the question is still Is y>0, but y<0 and the answer is a No.

However, if I choose x to be negative as well and we have y<0 which then tells us that x+y<0, and now the question is Is y<0 and the answer is Yes. Therefore, the statement 1 is insufficient. This is mentally a very difficult process, at least for me.

Now Statement (1) in the DS meets scenario (b)'s criteria. So does it make it sufficient? If we know y<0 does this imply x+y<0 and therefore (x-y)/(x+y)>1?

When we use multiple "if-then" scenarios does the question mark on the statement still extend?

In summary, the answer to your question is Yes.

(x-y)/(x+y)>1 ?? a) If x+y>0 which implies (x-y)>(x+y) ?? ---> y>0 ?? b) If x+y<0 which implies (x-y)<(x+y) ?? ----> y<0 ??

I hope this has clarified your original question.

Cheers, Dabral

gmatclubot

Re: If x does not equal -y is (x-y)/(x+y)>1?
[#permalink]
09 Jul 2013, 00:43

Last year when I attended a session of Chicago’s Booth Live , I felt pretty out of place. I was surrounded by professionals from all over the world from major...

I recently returned from attending the London Business School Admits Weekend held last week. Let me just say upfront - for those who are planning to apply for the...